Malaysian Consumer Awareness on 3D Printed Food - Lee , Kah Weng; Lee, Te Chuan (Research in Management of Technology and Business, 2025)
3D printing is important for achieving the goals of Industry 4.0. Malaysia has not yet adopted 3D food printing technology due to concerns about security, safety, and halal issues. Additionally, there is a lack of research on the awareness of 3D-printed food among Malaysian consumers. The research aims to measure the awareness level of 3D-printed food among Malaysian consumers and explore the connection between perceived benefits, knowledge of 3D-printed food, willingness to consume, and attitude towards 3D-printed food awareness in Malaysia. The scope of this study involves the analysis of awareness-level data using the Technology Acceptance Model and Diffusion of Innovation as independent variables and through a questionnaire. In this study, a quantitative approach was used to collect data via surveys, with the subsequent data analysis carried out using IBM SPSS software, and a total of 85 respondents participated in this research. Results show an average level of awareness of 3D-printed food among Malaysian consumers, with a mean score of 3.22. Results of the hypothesis testing revealed that the higher the perceived benefits, the better the awareness of 3D food printing, and the higher the knowledge of 3D-printed food, the better the awareness of 3D food printing; these hypotheses were accepted. However, the hypotheses that the higher the willingness to consume, the better the awareness of 3D food printing, and the higher the attitude, the better the awareness of 3D food printing were rejected. This research helps to understand consumers and assists the food industry and government in understanding Malaysian consumer acceptance levels for further enhancement.